Enhanced Nighttime Fog and Low Stratus Occurrence Over the Landes Forest, France. Issue 5 (1st March 2022) - Pauli, Eva; Cermak, Jan; Teuling, Adriaan J.
Abstract: Understanding the drivers of fog and low stratus (FLS) cloud occurrence is important for traffic, ecosystems, and climate models, but it is challenging to analyze due to the complex interactions between meteorological factors and land cover. Here, we use active and passive satellite data, as well as reanalysis data to investigate nighttime FLS occurrence over the expansive Landes forest in France from 2006 to 2015. We find significant FLS enhancement over the forest compared to surrounding areas, especially in summer and fall. Lower wind speed and lower temperatures are found over the forest at night, which can enhance FLS development over the forest. Still, other drivers, such as biovolatile organic compounds acting as cloud condensation nuclei, are most likely important as well. The results show that the influence of forests on boundary layer clouds is not limited to convective daytime conditions. Plain Language Summary: Fog and low stratus clouds (FLS) are influenced by various drivers. Their relationship to land cover, specifically forest, is thus difficult to investigate. In this study, we analyze nighttime FLS cover over a large forest area in south‐western France using a mix of different types of satellite data. We find higher FLS occurrence over the forest area compared to its surroundings, especially in summer and fall. Lower temperatures and wind speed over the forest could contribute to this enhancement. These results can help when predicting FLS for traffic and underline the importance of different land cover types for weather and climate. Key Points: Fog and low stratus (FLS) cloud cover is enhanced over the French Landes forest at night FLS cloud cover enhancement is most pronounced in summer and fall Low wind speed and low temperatures over the forest are potential drivers of FLS enhancement